Quantitative assessment of lung stiffness in patients with interstitial lung disease using MR elastography - Marinelli, John P.; Levin, David L.; Vassallo, Robert; Carter, Rickey E.; Hubmayr, Rolf D.; Ehman, Richard L.; McGee, Kiaran P. (Journal of magnetic resonance imaging, 2017)
Purpose To investigate the use of magnetic resonance elastography (MRE) in the quantitative assessment of pulmonary fibrosis by comparing quantitative shear stiffness measurements of lung parenchyma in patients diagnosed with fibrotic interstitial lung disease (ILD) and healthy controls. Materials and Methods A 1.5T spin‐echo, echo planar imaging MRE (SE‐EPI MRE) pulse sequence was utilized to assess absolute lung shear stiffness in 15 patients with diagnosed ILD and in 11 healthy controls. Data were collected at residual volume (RV) and total lung capacity (TLC). Spirometry data were obtained immediately prior to scanning. To test for statistical significance between RV and TLC shear stiffness estimates a two‐sample t‐test was performed. To assess variability within individual subject shear stiffness estimates, the intraclass correlation coefficient (ICC) and Krippendorff's alpha were calculated. Results Patients with ILD exhibited an average (±1 standard deviation) shear stiffness of 2.74 (±0.896) kPa at TLC and 1.32 (±0.300) kPa at RV. The corresponding values for healthy individuals were 1.33 (±0.195) kPa and 0.849 (±0.250) kPa, respectively. The difference in shear stiffness between RV and TLC was statistically significant (P < 0.001). At TLC, the ICC and alpha values were 0.909 and 0.887, respectively. At RV, the ICC and alpha values were 0.852 and 0.862, respectively. Conclusion In subjects with known fibrotic interstitial lung disease, parenchymal shear stiffness is increased when compared to normal controls at both RV and TLC, with TLC demonstrating the most significant difference. MRE‐derived parenchymal shear stiffness is a promising new noninvasive imaging‐based biomarker of interstitial lung disease. Level of Evidence: 1 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:365–374